Financial analysis as a strategic tool: the case of SMEs in the Republic of Kosova - Qehaja, Albana Berisha; Ismajli, Hysen (Business: Theory and Practice, 2018)
This paper examines the use of financial analysis as a strategic tool in SMEs. Empirical data are collected from 303 SMEs in the Republic of Kosova, operating in production, trade and service sectors. The aim of this study is to assess the extent to which the business financial analysis is employed in the sampled enterprises and to determine whether there are differences in the usage of it, within small and medium-sized enterprises and sectors. The results show that Kosovan SMEs greatly use financial analysis as a strategic tool. Moreover, significant differences are found between small and medium-sized enterprises regarding its usage and no significant differences among production, trade and service sectors. This paper contributes to the existing scientific literature, especially in the strategic management field. Additionally, this paper will likely contribute to decision makers’ increased use of business financial analysis as a strategic tool in their enterprises.